Formation of the demand for contraceptives using the Van Westendorp method based on establishing consumer value - T. V. Mahanova (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
One of the main indicators of the consumer value of a product is the price. Its controversial idealistic and materialistic basis is aimed at securing the interests of two opposites: producer-seller and buyer. Correctly made pricing decisions, taking into account the requirements of both players in the pharmaceutical market, will effectively regulate the processes of the pharmaceutical business and the supply system. The aim: approbation of the Van Westendorp method on the example of contraceptives; establishing their consumer value for further rational decision-making regarding the improvement of the system for providing contraceptives to Ukrainian female consumers.